The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1046/j.1464-410x.1998.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Metallic ureteric stents: early experience

Abstract: Objective To report our experience with metallic self-quality of life was improved and symptoms such as loin pain were ameliorated. Renal function was pre-expanding stents in the palliative care of patients with ureteric obstruction caused by advanced pelvic served; the mean serum creatinine level before and after stenting was 636 and 263 mmol/L, respectively). malignancy. Patients and methods Seven patients (five men and twoThe mean duration of stent patency was 9 months. Of the five patients who subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
(45 reference statements)
0
16
0
Order By: Relevance
“…In vitro studies with poly(ethylene oxide)/polyurethane composite hydrogel (Aquavene) showed promising results, with superior resistance to encrustation and intraluminal blockage over 24 weeks [18]. Other materials used recently as permanently implanted stents for relieving malignant obstructions and ureteral strictures are metallic, super-alloy, titanium or nickel/titanium stents designed to be covered by normal urothelium [1,29,40,42]. However, the extent to which epithelialization takes place remains to be seen.…”
Section: Urological Biomaterials and Biocompatibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies with poly(ethylene oxide)/polyurethane composite hydrogel (Aquavene) showed promising results, with superior resistance to encrustation and intraluminal blockage over 24 weeks [18]. Other materials used recently as permanently implanted stents for relieving malignant obstructions and ureteral strictures are metallic, super-alloy, titanium or nickel/titanium stents designed to be covered by normal urothelium [1,29,40,42]. However, the extent to which epithelialization takes place remains to be seen.…”
Section: Urological Biomaterials and Biocompatibilitymentioning
confidence: 99%
“…In the last few years, several clinical studies have focused on assessment of new implantable stents, which are expandable and permanent [1,29,30,40,42]. Time will tell if these can remain in the host without becoming a nidus for infections, encrustation, toxicity, and other adverse eects.…”
Section: Design Shape And¯ow Studiesmentioning
confidence: 99%
“…Gort et al [20] reported the first use of a metallic ureteric stent and since then a variety of stents have entered urological practice, e.g. wallstents, PalmazSchatz and Accuflex stents [21] . However, these are all meshed stents and their usage is hindered by re-occlusion due to endothelial hyperplasia, and tumour in-growth through the meshwork making removal virtually impossible [22,23] .…”
Section: Introductionmentioning
confidence: 99%
“…Patency was maintained for 6 months. Pandian et al [10] reported their early experience with antegrade placement of the Memotherm stent which does not have the property of softening and cannot be removed. Wallstents have also been described in treating ureteral strictures.…”
Section: Discussionmentioning
confidence: 99%